Anticapitalism and the emergence of antisemitism - Chasin, Stephanie M. (Peter Lang, 2020)
The shadowy realm of usury -- The purses and leeches of princes -- The filthy rich -- In the name of God and profit -- The banker's charter and the national Interest -- A dangerous game of monopoly -- The virtue of vice -- The "regeneration" of Jewish usurers -- The globalization of capital -- Sharing the wealth -- The tyranny of usury conspiracy -- Mr. moneybags.